Analysis Of Community And Practitioner Perceptions Of Biopori-Based Water Treatment Technologies In The Context Of Flood Resistance - Rahmawati; Nurhapsa; Fahmi, Ahmad (UIR PRESS, 2024)
This study explores the differences in perception between communities and practitioners regarding biopori-based water management technology in the context of flood management in Passeno Village, Baranti District, Sidenreng Rappang Regency, South Sulawesi Province, Indonesia. Employing a quantitative approach, the study involved 30 respondents, consisting of 27 members of farmer groups and 3 practitioners. Data were collected through surveys using structured questionnaires and analyzed using descriptive and inferential statistical techniques. The results indicated that communities rated the effectiveness and ease of implementation of biopori technology higher than practitioners did. The main obstacles identified were a lack of knowledge and government support, with proposed solutions including intensive investigations and government subsidies. Although no significant differences in perception were found between the two groups, this study emphasizes the importance of education, government support, and field experience in influencing the acceptance of biopori technology. The uniqueness of this research lies in its specific focus on biopori technology, the rare comparison of perceptions between communities and practitioners, and its systematic quantitative approach. Additionally, the study successfully identifies obstacles and practical solutions while encouraging better collaboration between communities and practitioners, thereby potentially providing significant contributions to policies and practices in water resource management in flood-prone areas.